The long pentraxin 3 in cardiac surgery: distinct responses in "on-pump" and "off-pump" patients - Kunes, Pavel; Lonsky, Vladimir; Mandak, Jiri; Kolackova, Martina; Andrys, Ctirad; Kudlova, Manuela; Krejsek, Jan (Scandinavian cardiovascular journal, 2007)
OBJECTIVE: Pentraxin 3 (PTX3) is a newly identified acute phase reactant with non-redundant functions in innate immunity. The purpose of this study was to assess the kinetics of release of PTX3 in cardiac surgical patients, operated on either with or without the use of cardiopulmonary bypass (CPB). DESIGN: Thirty-four patients, seventeen in each group, were randomly assigned to CABG surgery performed either with ("on-pump") or without ("off-pump") CPB. Blood samples were collected both during and after the operation up to the 7(th) day. RESULTS: In patients operated on with the use of CPB, PTX3 levels increased throughout the operation. Compared to baseline levels the highest PTX3 value (p<0.000) was attained on the 1(st) postoperative day in both "on-pump" and "off-pump" patients. In contrast to CPB patients, however, PTX3 levels in the latter group declined slowly, remaining elevated as long as the 3(rd) postoperative day (p<0.042). CONCLUSIONS: Operations performed with the use of CPB are associated with a more pronounced release of PTX3 immediately after operation.
Keywords: Humans; Coronary Artery Bypass; lidé středního věku; C-reaktivní protein; Female; Aged; Cardiopulmonary Bypass; Interleukin-10; Interleukin-6; výsledek terapie; Coronary Artery Bypass, Off-Pump; senioři; koronární bypass bez mimotělního oběhu; lidé; Biomarkers; Serum Amyloid P-Component; kardiopulmonální bypass; Kinetics; biologické markery; ženské pohlaví; Male; Middle Aged; koronární bypass; interleukin-6; Treatment Outcome; sérový amyloidový protein; interleukin-10; mužské pohlaví; C-Reactive Protein; kinetika